THE DEFINITION OF RATIONAL MODES OF UNCOUPLED CARS ROLLING DOWN FROM HUMPS - Kudriashov, A. V. (Science and Transport Progress, 2009)
Researches are executed and the method of choice of rational parameters of the mode of braking of guided cut in a group of three cuts with the set numbers of dividing switches is developed. The method is aimed at the solution of optimization task of modes of braking the rolling stock cuts.